Two Algorithms for Web Applications Assessment - Valsamidis, Stavros Ioannis; Kontogiannis, Sotirios; Karakos, Alexandros Spiros (International Journal of Emerging Technologies in Learning (iJET), 2011)
The usage of web applications can be measured with the use of metrics. In a LMS, a typical web application, there are no appropriate metrics which would facilitate their qualitative and quantitative measurement. The purpose of this paper is to propose the use of existing techniques with a different way, in order to analyze the log file of a typical LMS and deduce useful conclusions. Three metrics for course usage measurement are used. It also describes two algorithms for course classification and suggestion actions. The metrics and the algorithms and were in Open eClass LMS tracking data of an academic institution. The results from 39 courses presented interest insights. Although the case study concerns a LMS it can also be applied to other web applications such as e-government, e-commerce, e-banking, blogs e.t.c.